Pengaruh Model Pembelajaran Sinektik Terhadap Kemampuan Menulis Puisi Siswa Kelas X Sman 1 Wanasari Kabupaten Brebes - Hany Uswatun Nisa; Renastasya Larastanti; Ghufroni Ghufroni (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study generally aims to determine the level of success and ability of students to practice writing poetry through the application of the synectic model. In particular, this study aims to determine the effect of applying the synectic learning model on the ability to write poetry for class X students of SMAN 1 Wanasari. The research was conducted using an experimental method with a pretest-posttest control group design. The research was conducted on class X students at SMAN 1 Wanasari Brebes. The research population consisted of 6 classes with 256 students. The research sample was taken as many as 2 classes with cluster random sampling technique. Data obtained by test consisting of pretest and posttest. Data analysis used the t-test formula with prerequisite tests including normality and homogeneity tests. Based on the results of the analysis and discussion, this study concluded that there was an effect of the synectic learning model on the ability to write poetry in class X SMAN 1 Wanasari, Brebes Regency.